Potential international employment effects of a hard Brexit - Hans-Ulrich Brautzsch; Oliver Holtemöller (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2019)
We use the World Input Output Database (WIOD) to estimate the potential employment effects of a hard Brexit in 43 countries. In line with other studies we assume that imports from the European Union (EU) to the UK will decline by 25% after a hard Brexit. The absolute effects are largest in big EU countries which have close trade relationships with the UK like Germany and France. However, there are also large countries outside the EU which are heavily affected via global value chains like China, for example. The relative effects (in percent of total employment) are largest in Malta and Ireland. UK employment will also be affected via intermediate input production. Within Germany, the motor vehicle industry and in particular the 'Autostadt' Wolfsburg are most affected.
urn:nbn:de:gbv:3:2-104045
Keywords: C67; D57; F16; R15; 330; Brexit; employment; European Union; international trade; tariffs